Subzero cell division, respiration, and genomic traits of cryophilic Arthrobacter agilis Ant-EH-1 isolated from cold-arid Antarctic mineral soils - Wood, Claudia; Magnuson, Elisse; Harrop, Ethan; Trembath-Reichert, Elizabeth; Wilhelm, Mary Beth; Goordial, Jacqueline (Frontiers in Microbiology, 2025)
Arthrobacter are commonly isolated from cold soil environments globally, including those that regularly reach sub-freezing temperatures, suggesting that Arthrobacter have significant potential for growth and activity under temperature and stress extremes. Arthrobacter agilis strain Ant-EH-1 was isolated from nutrient-poor, cold-arid mineral soils from Elephant Head, Antarctica and its growth and activity at sub-freezing temperatures were characterized in this study. We observed different optimal temperatures for cell division compared with aerobic heterotrophic respiration in A. agilis Ant-EH-1. Cell division was observed from at least −5 °C to 30 °C, with the optimal (fastest) growth rate occurring at 25 °C. Microbial respiration was measured from −5 °C to 30 °C with optimal (maximum CO2 produced) respiration occurring at 5 °C. Cold temperature optima of respiration compared with cell division could be indicative of adaptation to the cold and oligotrophic conditions of Elephant Head, where increased cell division under in situ conditions could lead to competition within the nutrient-poor soil matrix. The genome of A. agilis Ant-EH-1 was consistent with observations of cold-adapted activity and included genes related to cold stress, osmotic and oxidative stress, pigment biosynthesis, and potential scavenging of components from necromass. Microscopy revealed morphological differences in this isolate at sub-freezing temperatures, likely due to membrane or lipid modifications. Currently there are a limited number of organisms in culture that are capable of sub-zero growth, so characterisation of the growth and activity of subfreezing adapted microbiota is critical for understanding the ecology of Earth’s cryosphere, has broad biotechnological potential, and can also give insight into the limits for life on our planet or the potential for life on other cold planetary bodies.